(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2023)
This article deals with one of the most essential issues in methodology. Modern a foreign language classroom should contain the latest IT tools to make lesson more interesting and involving. Movies aren’t just for entertainment in a foreign language class; they also give you a cultural education that enriches your language comprehension. Movies also expose you to a more natural form of the language with authentic vocabulary and slang, and they teach you to connect words with associated body language. This article focuses on a number of characteristic features of films as a foreign language teaching material and shows some ways to use it to develop language skills of learners.